2006
DOI: 10.1891/088970106805074421
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Learning Communities to Promote Full Inclusion of Students with Disabilities on College and University Campuses

Abstract: Students with disabilities are enrolling in and completing higher education at unprecedented rates. However, in comparison to their peers without disabilities, they are not receiving comparable benefits from their education (e.g. full-time jobs, employment commensurate with their education). Because of their specialized knowledge and skills, rehabilitation educators are in unique positions to take the lead in providing guidance to their colleagues regarding how to better prepare students with disabilities to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Even though students with disabilities are enrolling in college at higher rates, they earn lower grades in college than their peers without disabilities (Wehman, 2001), take longer to complete their degrees (Brinckerhoff, McGuire, & Shaw, 2002), have a higher dropout rate (Rumrill, 2001), and are more likely to be unemployed (Roessler, Hennessey, & Rumrill, 2007). Furthermore, research has shown that for students with disabilities, having a college education does not guarantee a successful career (Koch, Hennessey, Ingram, Rumrill, & Roessler, 2006) because the employment rate of students with disabilities is lower than the employment rate of students without disabilities (Collet-Klingenberg, 1998;Dunn, 1996). Despite this outcome, students with disabilities continue to represent an increasing proportion of today's college students (Burgstahler, 2001).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though students with disabilities are enrolling in college at higher rates, they earn lower grades in college than their peers without disabilities (Wehman, 2001), take longer to complete their degrees (Brinckerhoff, McGuire, & Shaw, 2002), have a higher dropout rate (Rumrill, 2001), and are more likely to be unemployed (Roessler, Hennessey, & Rumrill, 2007). Furthermore, research has shown that for students with disabilities, having a college education does not guarantee a successful career (Koch, Hennessey, Ingram, Rumrill, & Roessler, 2006) because the employment rate of students with disabilities is lower than the employment rate of students without disabilities (Collet-Klingenberg, 1998;Dunn, 1996). Despite this outcome, students with disabilities continue to represent an increasing proportion of today's college students (Burgstahler, 2001).…”
Section: Overviewmentioning
confidence: 99%
“…Students with disabilities are attending college at a higher rate than in previous years (Koch et al, 2006;Stodden, Whelley, Chang, & Harding, 2001); however, their success rate in college and post college has not increased. Multiple studies have demonstrated that college graduates with disabilities are more likely to be unemployed than graduates without disabilities (American Council on Education [ACE], 1999;DeLoach, Sparger, & Pullen, 1988;Frank, Karst, & Boles, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Despite difference in terminology all methodologies are based on implementation of UD principles in education; they are not contradictious and do not compete one with other (Higbee & Goff, 2008). Quite often these headings in scientific literature and research works are used alternately (Koch, 2006), but in other sources (McGuire, 2006) there is described differences between them. All three educational models are focused on implementation of flexible UD principles corresponding learning programs and eISSN: 2357-1330 Selection & Peer-review under responsibility of the Conference Organization Committee 108 pedagogical techniques, which would ensure students' needs for diversity from lesson objectives and materials to instructional methods and assessments (Hall, Meyer, & Rose, 2012).…”
Section: Problem Statementmentioning
confidence: 99%